Pre-service EFL teachers' reported perceptions of their development through SETT experience. Issue 2 (3rd May 2016) - Aşık, Asuman; Kuru Gönen, S. İpek
Abstract: Recent years have witnessed increasing attention to the role of interaction in the classroom. Regarding the dynamic nature of language classrooms, teacher talk is assumed to promote interaction. Based on this assumption, this paper aims at investigating EFL teachers' perceptions of their use of teacher talk and how analysis of language use contributes to their professional development. For this purpose, a total of 23 pre-service teachers from ELT departments of two universities in Turkey participated in the study. They received training on analysis of their own talk by using a specific instrument (SETT) designed to assess relationship between language use and pedagogic purpose. The pre-service teachers recorded snapshots of their teaching to analyse different interactional features of their talk, organised peer sessions to discuss each other's language use and wrote three reflective diaries. Two raters coded qualitative data using the Constant Comparison Method. Results indicated that the SETT experience helped them to increase awareness of what they did, how they did it and how they used language in the classroom environment. The findings offer valuable insights about teachers' language use and its effects on the development of classroom interaction.